About a place in the Kinki region - Sesuji (Horror fiction writer) (Yen On, 2025)
"My friend is missing. When he disappeared, he'd been working on a magazine about the paranormal--his first real job as an editor. With almost no budget, he'd resorted to digging through back issues and unused research material, looking for inspiration. As he did, a terrifying truth began to emerge about a certain place in the Kinki region. I have collected the relevant articles, interviews, and other materials in this book. And once you have understood everything, I would like to ask for your cooperation. I hope you will get in touch"-- Provided by publisher.